A Critical Review of “Ibn-Sina’s Influence on Dons Scotos” - Hassan Fathi (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
Islamic philosophy in its first formation has been widely influenced by Christian philosophy. After several centuries, however, Islamic world takes the upper hand, and Islamic scientific and philosophical school influenced the Christian ones, especially and intensely in so-called Scholastic era. The most influencing figure, from this point of view, was Avicenna. Avicenna’s Influence on Duns Scotus’ Philosophy, by Mahdi Abbaszade, intends to expose an example of the aforesaid influences, as a case study: Avicennna’s on Duns Scotus. Abbaszade’s book is relatively comprehensive and very informative. Dr Abbaszade could have a better work by seeing all of scotus’ philosophical writings, and by refraining from some prejudices and exaggerations.